ANALISIS USER INTERFACE DAN USER EXPERIENCE DENGAN MENGGUNAKAN METODE USER CENTERED DESIGN PADA APLIKASI BRIMO (BRI MOBILE) - Muhammad Restu Alfiansyah (2022)
Bank BRI is one of the banks in Indonesia that has provided the best services with digitalization services to its customers. One of BRI's innovations with digitalization services is BRImo (BRI Mobile), which is still being developed. The information system on the BRImo application has never been analyzed regarding how users think about the interface of the BRImo application and how the user experiences when using the application with certain methods. This study aims to analyze the user interface and user experience of the BRImo application using an approach method, namely User Centered Design (UCD) with System Usability Scale (SUS) techniques to determine usability values and user testing using maze tools to make it easier to get test results. This research produces a new interface in the form of a prototype that can be used as evaluation material and suggestions for the BRImo application with an increase in the usability value of 17 so that users can have a good experience when using the BRImo application.